The Role of Iron-Deficiency Stress Responses in Stimulating Heavy-Metal Transport in Plants - Cohen, Clara K. (American Society of Plant Physiologists, 1998)
Plant accumulation of Fe and other metals can be enhanced under Fe deficiency. We investigated the influence of Fe status on heavy-metal and divalent-cation uptake in roots of pea (Pisum sativum L. cv Sparkle) seedlings using Cd(2+) uptake as a model system. Radiotracer techniques were used to quantify unidirectional (109)Cd influx into roots of Fe-deficient and Fe-sufficient pea seedlings. The concentration-dependent kinetics for (109)Cd influx were graphically complex and nonsaturating but could be resolved into a linear component and a saturable component exhibiting Michaelis-Menten kinetics. We demonstrated that the linear component was apoplastically bound Cd(2+) remaining in the root cell wall after desorption, whereas the saturable component was transporter-mediated Cd(2+) influx across the root-cell plasma membrane. The Cd(2+) transport system in roots of both Fe-deficient and Fe-sufficient seedlings exhibited similar Michaelis constant values, 1.5 and 0.6 μm, respectively, for saturable Cd(2+) influx, whereas the maximum initial velocity for Cd(2+) uptake in Fe-deficient seedlings was nearly 7-fold higher than that in Fe-grown seedlings. Investigations into the mechanistic basis for this response demonstrated that Fe-deficiency-induced stimulation of the plasma membrane H(+)-ATPase did not play a role in the enhanced Cd(2+) uptake. Expression studies with the Fe(2+) transporter cloned from Arabidopsis, IRT1, indicated that Fe deficiency induced the expression of this transporter, which might facilitate the transport of heavy-metal divalent cations such as Cd(2+) and Zn(2+), in addition to Fe(2+).